CO2 Has no Therapeutic Effect on Early Micro Vasospasm after Experimental Subarachnoid Hemorrhage. Issue 8 (August 2014) - Friedrich, Benjamin; Michalik, Radoslaw; Oniszczuk, Anna; Abubaker, Khalid; Kozniewska, Ewa; Plesnila, Nikolaus
In addition to delayed vasospasm also early brain injury, which occurs during the first few days after subarachnoid hemorrhage (SAH) when large cerebral arteries are still fully functional, plays an important role for the outcome after SAH. In the current study, we investigated the hypothesis that carbon dioxide (CO2 ), a strong cerebral vasodilator, has a therapeutic potential against early posthemorrhagic microvasospasm. C57BL/6 mice ( n = 36) and Sprague-Dawley rats ( n = 23) were subjected to sham surgery or SAH by filament perforation. The pial microcirculation in the mice was visualized 3 and 24 hours after SAH using intravital fluorescence microscopy. Partial pressure of CO2 (PaCO2 ) was modulated by hyper- or hypoventilation or by inhalation of 10% CO2 . In rats, CO2 -mediated changes in cerebral blood flow (CBF) were measured at the same time points using laser Doppler fluxmetry. Increased PaCO2 caused vasodilatation in sham-operated animals. Following SAH, however, cerebral arterioles were nonreactive to CO2 . This lack of microvascular CO2 reactivity was accompanied by a complete loss of CO2 -induced hyperemia. Our data show that CO2 is not able to dilate spastic microvessels and to increase CBF early after SAH. Future therapeutic approaches will therefore need to address mechanisms beyond CO2 .